Pengaruh Adverse Childhood Experience terhadap Tingkat Intimate Partner Violence pada Dewasa Muda - Ghaisyani Rizky Dwiagustin Handoko; Naomi Soetikno (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2025)
This study aims to analyse the influence of Adverse Childhood Experiences (ACEs) on Intimate Partner Violence (IPV) in young adults. ACEs include negative childhood experiences such as abuse, neglect, and family dysfunction, which have the potential to affect psychological development and the quality of interpersonal relationships in adulthood. IPV refers to various forms of violence in intimate relationships, including physical, psychological, sexual, and controlling behaviours. This study uses a quantitative approach with purposive sampling techniques involving 318 young adult respondents. The instruments used were the ACEs scale and the Conflict Tactics Scale 2 (CTS2). Data analysis was conducted through tests of validity and reliability, normality tests, nonparametric regression using Quantile Regression, as well as Mann–Whitney and Kruskal–Wallis tests. The results indicate that ACEs have a positive and significant effect on IPV (β = 2.214; p < 0.001).  Most respondents were in the moderate ACEs category (73.6%) and moderate IPV (53.8%). These findings underscore the importance of trauma-based preventive interventions in young adults.